If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -10x = -18 Reorder the terms: -10x + 2y = -18 Solving -10x + 2y = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -10x + 2y + -2y = -18 + -2y Combine like terms: 2y + -2y = 0 -10x + 0 = -18 + -2y -10x = -18 + -2y Divide each side by '-10'. x = 1.8 + 0.2y Simplifying x = 1.8 + 0.2y
| 2w+2(2w-40)=220 | | 121m^2-49=0 | | -3-9y=-25 | | 1/2x-8=16 | | 10=5(m-2) | | Y-7=-14(x-9) | | 3c-b/c=a | | x-9y=-7 | | s/2-8=6 | | 2x-4=-3x-6 | | 211-6x=30x+19 | | 35-6x=3x+20 | | 3k/5+44=12k/2+58 | | 76-5x=40x+16 | | 9-0.5=1.5 | | 2(3b-2)=4b | | -7x/12=-1/6 | | A1B1/C1=A2B2/C2 | | 6x+4=-10 | | 6(q-4)=64 | | 4x^2-9x+9=3x+4 | | 2/5(5x-15)=4 | | f(x)=x^3+16x^2-19x-10 | | r-(-1.2)=7.3 | | 5m+6m+8m-5= | | 6(4-2e)-3(5+3e)= | | b+5b=42 | | 54/3^2*6(6-3) | | 13c-52= | | 6x+33=16x+3 | | 4r-1whenr=9 | | 4.6x-12.1=10.9 |